Possible solution to smoothen the nature of the torque curve of the CAMPRO engine - Mohiuddin, A. K. M.; Rahman, Mohammed Ataur; Arfah, A,; Farraen, M.A. (Inderscience Enterprises Ltd., 2011)
The objective of this paper is to develop new solutions to smooth the torque curve of the CAMPRO engine. The authors have performed an extensive study on the causes of the torque dip in CAMPRO engine. The CAMPRO engine experiences performance downfall when it reaches 2,500 to 3,500 rpm. The main objective of this work is to perform an extensive study on the causes of the dip in CAMPRO engine and subsequently to provide the best solution. Analysis shows that at the point of dip a downfall of the volumetric efficiency also occurs. In order to enhance the volumetric efficiency and to eliminate the torque dip, two parameters were considered, viz., runner length and diameter and valve timing. In this paper, focus is given on the length of intake manifold. From the analysis done, two possible solutions were provided viz., natural dual intake manifold and continuous variable intake manifold.